Hardship and Humanity: A Closer Qualitative Look at Surgical Training and Its Effects on Trainees From the Perspectives of Loved Ones. Issue 4 (29th April 2022) - Kemp, Michael T.; Evans, Julie; Rivard, Samantha J.; Sharma, Sriganesh B.; Williams, Aaron M.; Coleman, Dawn M.; Dimick, Justin; Sandhu, Gurjit
Abstract : Objective: The aim of this study was to obtain novel perspectives regarding the effects that surgical training has on the well-being of trainees. Summary Background Data: Improving trainee well-being is a national concern given high rates of burnout, depression, and suicide among physicians. Supporters of surgical trainees may offer new perspectives regarding the effects of surgical training and point to strategies to optimize trainee wellness. Methods: This qualitative study employs semi-structured interviews of 32 support persons of trainees at a single tertiary care center with multiple surgical training programs. Interviews focused on perspectives related to supporting a surgical trainee. Interview transcripts underwent qualitative analysis with semantic and conceptual coding. Themes related to effects of training on trainee wellness are reported. Results: Four themes were identified: Who Can Endure the Most Hardship?—trainee attributes and programmatic factors contribute to trainees feeling the need to constantly endure the most hardship; Consequences of Hardship—constantly enduring hardships has significant negative effects on wellness; Trainees are Humans—trainees are people with basic human needs, especially the need for worth; Research Time as Refuge—dedicated research time is treated as an oasis away from clinical hardships. Conclusions: Perspectives from support persons can offer valuable insight into the wellness needs of surgical trainees. According to support persons, surgical training profoundly negatively impacts trainee wellness. Unlike during clinical training, dedicated research time is a period during which wellness can be prioritized. Programs should provide greater attention to mitigating the negative ramifications of surgical training and promoting wellness in a longitudinal fashion throughout training.